Blood Purification and Mortality in Sepsis and Septic Shock: A Systematic Review and Meta-analysis of Randomized Trials. (September 2019) - Putzu, Alessandro; Schorer, Raoul; Lopez-Delgado, Juan Carlos; Cassina, Tiziano; Landoni, Giovanni
Editor's Perspective: What We Already Know about This Topic: Among patients with sepsis or septic shock, a variety of extracorporeal blood purification techniques are available Individual existing trials evaluating these options are underpowered to provide clear evidence What This Article Tells Us That Is New: Meta-analysis of very low-quality randomized controlled trial evidence demonstrates a potential benefit of hemoperfusion, hemofiltration, or plasmapheresis Additional high-quality trials demonstrating benefit in modern clinical practice are needed before recommending these therapies Background: Sepsis and septic shock are severe inflammatory conditions related to high morbidity and mortality. We performed a systematic review with meta-analysis of randomized trials to assess whether extracorporeal blood purification reduces mortality in this setting. Methods: Electronic databases were searched for pertinent studies up to January 2019. We included randomized controlled trials on the use of hemoperfusion, hemofiltration without a renal replacement purpose, and plasmapheresis as a blood purification technique in comparison to conventional therapy in adult patients with sepsis and septic shock. The primary outcome was mortality at the longest follow-up available. We calculated relative risks and 95% CIs. The grading of recommendations assessment, development and evaluation methodology for the certainty of evidence was used. Results: Thirty-seven trials with 2, 499 patients were included in the meta-analysis. Hemoperfusion was associated with lower mortality compared to conventional therapy (relative risk = 0.88 [95% CI, 0.78 to 0.98], P = 0.02, very low certainty evidence). Low risk of bias trials on polymyxin B immobilized filter hemoperfusion showed no mortality difference versus control (relative risk = 1.14 [95% CI, 0.96 to 1.36], P = 0.12, moderate certainty evidence), while recent trials found an increased mortality (relative risk = 1.22 [95% CI, 1.03 to 1.45], P = 0.02, low certainty evidence); trials performed in the United States and Europe had no significant difference in mortality (relative risk = 1.13 [95% CI, 0.96 to 1.34], P = 0.15), while trials performed in Asia had a positive treatment effect (relative risk = 0.57 [95% CI, 0.47 to 0.69], P < 0.001). Hemofiltration (relative risk = 0.79 [95% CI, 0.63 to 1.00], P = 0.05, very low certainty evidence) and plasmapheresis (relative risk = 0.63 [95% CI, 0.42 to 0.96], P = 0.03, very low certainty evidence) were associated with a lower mortality. Conclusions: Very low-quality randomized evidence demonstrates that the use of hemoperfusion, hemofiltration, or plasmapheresis may reduce mortality in sepsis or septic shock. Existing evidence of moderate quality and certainty does not provide any support for a difference in mortality using polymyxin B hemoperfusion. Further high-quality randomized trials are needed before systematic implementation of these therapies in clinical practice. Abstract : Meta-analysis of very low-quality randomized controlled trial evidence demonstrates a potential benefit of hemoperfusion, hemofiltration, or plasmapheresis. Additional high-quality trials demonstrating benefit in modern clinical practice are needed before recommending these therapies.Supplemental Digital Content is available in the text.